The genus Phantolabis (Diptera: Limoniidae) new to the Palearctic: description of a new species and re-definition of the genus - Pilipenko, Valentin E. (European Journal of Taxonomy, 2021)
A new crane fly species from the genus Phantolabis Alexander, 1956, active in the cold season and previously known by a single, eastern Nearctic species, is described from Primorsky Krai of the Russian Far East. A revised definition of the genus is given.